HOW HEALTH BELIEF OF DIABETES MELLITUS TYPE 2 IN ADHERENCE CONSUME DRUG: A PHENOMENOLOGY STUDY - Istianna Nurhidayati; Arlina Dhian S; Mawardi Mawardi; Fia Nur Haryani (Universitas Respati Yogyakarta, 2022)
Adherence of people with type 2 diabetes mellitus in taking medication is the key to successfully managing type 2 diabetes mellitus. People with DM have the ability to control their disease obediently to taking medication which is influenced by the ability to understand perceptions of health beliefs. The aims of this study was explored understanding health beliefs of patients with type 2 diabetes mellitus in adherence to taking medication. This study used a qualitative design with a phenomenological approach. This study used 7 participants. Analyzed data used Colaizzi with thematic analysis manually. The results of the study obtained 14 themes about the health trust of patients with type 2 diabetes in adherence taking medication. The fourteen themes ware knowledge about type 2 diabetes mellitus, signs and symptoms of type 2 diabetes mellitus, causes of increased blood sugar, how to regulate blood sugar, adherence with medication, adherence motivation to take medication, diabetes mellitus type 2 is at risk, measures to reduce type of diabetes mellitus 2, the severity of type 2 diabetes mellitus, the body is more stable, the time to take medicine, the obligation and feeling of the body, acceptance of family and sincerity, and the hope of people with type 2 diabetes mellitus on quality health services. The conclusion of this study was perceptions of health beliefs of patients with type 2 diabetes mellitus who good can improve medication adherence. It happens because of the perception of vulnerability, seriousness, obstacles, cues to act and perceived benefits and good self-confidence so that people with type 2 diabetes mellitus choose to obey taking medication. Keywords: Health belief, medication adherence, type 2 diabetes mellitus.